Prediction of Building Permit Approval in Medan City Using the Naïve Bayes Algorithm for Investment Prospects - Parhusip, Nelviony; Muhammad Iqbal (Journal Of Data Science, 2025)
Property investment in Medan City has become increasingly important in line with economic growth and rapid infrastructure development. Over the past decade, property investment in Medan has shown significant growth, as evidenced by the expansion of residential areas, boarding houses, hotels, and integrated apartments such as Manhattan Square, Jati Junction, and Podomoro Deli Park. This study aims to predict and identify patterns of Building Permit Approval (PBG) in Medan City that are significantly related to investment prospects. The algorithm used in this study is Naïve Bayes, implemented using the Orange tool, which enables the prediction of building permit approvals in Medan City. The key findings of this study indicate the existence of significant building permit approval patterns and the identification of potential investment areas. The implications of this research are crucial for investors and developers in formulating more effective investment strategies